Effects of tillage methods and sowing rates on the grain yields and yield components of rain fed wheat - Shamsabadi, Hossein T.; Biabani, A.; Ahmad, Desa (Universiti Putra Malaysia Press, 2009)
A field study was conducted on the effect of four primary tillage implements and three seed densities on the grain yield of rain fed wheat (Tajan cultivar), using a drill planting machine with the end wheels. The experimental design was a split plot design in a 4Ã—3 factorial with three replications. In this study, the main plots were the tillage treatments, namely Mouldboard plough, Disc Plough, Chisel Plough, Offset Disc, and sub-plots were seed rates of 350, 400 and 450 seeds.m-2-2 sowing rate, had the highest grain yield of wheat grown in the Golestan province (Iran), a region with an average annual rainfall of 450 mm.